A new view from La Cotte de St Brelade, Jersey. (March 2014) - Scott, Beccy; Bates, Martin; Bates, Richard; Conneller, Chantal; Pope, Matt; Shaw, Andrew; Smith, Geoff
Abstract : Did Neanderthal hunters drive mammoth herds over cliffs in mass kills? Excavations at La Cotte de St Brelade in the 1960s and 1970s uncovered heaps of mammoth bones, interpreted as evidence of intentional hunting drives. New study of this Middle Palaeolithic coastal site, however, indicates a very different landscape to the featureless coastal plain that was previously envisaged. Reconsideration of the bone heaps themselves further undermines the 'mass kill' hypothesis, suggesting that these were simply the final accumulations of bone at the site, undisturbed and preserved in situ when the return to a cold climate blanketed them in wind-blown loess.